113k views
5 votes
Which of the following is a solution of y - x > -3?

(6, 2)
(2, 6)
(2, -1)

User Mszaro
by
4.3k points

2 Answers

4 votes

Answer:2 - 6 = -4 . . . . not > -3

6 - 2 = 4 . . . . . is > -3. This is a solution.

-1 -2 = -3 . . . . .not > -3

The point (2, 6) is a solution.

Explanation:

User Josh Mein
by
5.7k points
3 votes
2 - 6 = -4 . . . . not > -3
6 - 2 = 4 . . . . . is > -3. This is a solution.
-1 -2 = -3 . . . . .not > -3

The point (2, 6) is a solution.
User Dimitry Ernot
by
5.4k points